2023
DOI: 10.1182/bloodadvances.2022009124
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous adjunctive treatment of malaria and its coevolved genetic disorder sickle cell anemia

Abstract: Effective treatments for genetic disorders that co-evolved with pathogens require simultaneous betterment of both conditions. Hydroxyurea (HU) offers safe and efficacious treatment for sickle cell anaemia (SCA) by reducing clinical complications, transfusions, and death. Despite concerns that HU-treatment for SCA would increase infection risk by the human malaria Plasmodium falciparum, (the genetic driver of the sickle mutation), HU instead reduced clinical malaria. We utilized physiologically relevant drug ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In addition, Safeukui et al recently demonstrated hydroxyurea and other ribonucleotide reductase inhibitors reduce schizont development by nearly 40% in HbSS erythrocytes. 40 A question remains, however, whether HbF could increase the risk of malaria in select individuals, particularly infants and those with known congenital or GT-modified HbF inducers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Safeukui et al recently demonstrated hydroxyurea and other ribonucleotide reductase inhibitors reduce schizont development by nearly 40% in HbSS erythrocytes. 40 A question remains, however, whether HbF could increase the risk of malaria in select individuals, particularly infants and those with known congenital or GT-modified HbF inducers.…”
Section: Discussionmentioning
confidence: 99%
“…In a secondary analysis of the subjects in the REACH study, the authors found that participants had a lower incidence of malaria after starting hydroxyurea therapy compared with prior treatment. In addition, Safeukui et al recently demonstrated hydroxyurea and other ribonucleotide reductase inhibitors reduce schizont development by nearly 40% in HbSS erythrocytes 40 . A question remains, however, whether HbF could increase the risk of malaria in select individuals, particularly infants and those with known congenital or GT‐modified HbF inducers.…”
Section: Discussionmentioning
confidence: 99%
“… 20 In murine models, hydroxyurea decreased parasitemia, prevented experimental cerebral malaria, 21 and had direct activity against schizont stages of malaria. 22 Together, these data suggest that hydroxyurea may have both immunomodulatory and antimicrobial effects that reduce the risk of infections.…”
mentioning
confidence: 96%
“…In this issue of Blood Advances , Safeukui et al demonstrate the antimalarial properties of hydroxyurea, a ribonucleotide reductase (RNR) inhibitor, found to be a safe and efficacious therapy used to manage sickle cell disease (SCD) in children and adults. 1 The World Health Organization estimates that a child dies of malaria every 2 minutes. 2 In addition, SCD, a deadly inherited hemoglobinopathy, characterized by severe anemia and painful vaso-occlusive crises resulting in pain and/or end-organ dysfunction, affects over 300 000 newborns annually, 3 predominantly in regions endemic for malaria.…”
mentioning
confidence: 99%